Menumbuhkan Minat Belajar Sains Biologi dengan Bantuan Media Pembelajaran Animasi Macromedia Flash: Studi Quasi Eksperimen - Ririn Rostanti Ciuda (Al-Nafis: Jurnal Biologi dan Pendidikan Biologi, 2021)
Applying interesting learning through the help of media is a way to stimulate students' interest in learning. However, it is very rare to find research that explores students' learning interests. This study aims to investigate the effect of using macromediaflash on students' learning interest. A quasi-experimental design with a control group and an experimental group was used. A total of 44 junior high school students aged 11 to 13 years participated in this study. They were divided into two groups, namely the experimental group which received learning treatment with the help of macromedia flash (experimental) and the control group received treatment with conventional strategies without the help of media. Interest in learning data obtained through a questionnaire and analyzed by t-test. The findings of this study indicate that students in the experimental class who are exposed to fun learning with the help of macromedia flash get a higher learning interest score compared to students in the control class without the help of media. The findings of this study reveal that the use of macromedia flash in learning can be an effective way to increase students' interest in learning